2005
DOI: 10.1007/bf03026328
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of hip fracture in Japan: incidence and risk factors

Abstract: Hip fracture is the most serious complication of osteoporosis and has been recognized as a major public health problem. The prevention of hip fractures is an high-priority issue because of the rapid increase of the number of elderly people in Japan. The General Research Committee for the Prevention and Treatment of Osteoporosis in Silver Health Science Researches sponsored by the Ministry of Health and Welfare (Director, Hajime Orimo) first undertook a nationwide survey of femoral neck fracture in 1987. This n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 5 publications
0
21
0
3
Order By: Relevance
“…Another report from Japan declared that more than 40% of falls among the elderly caused fractures 23 . Our results revealed that most hospitalizations of elderly falling were treated by the orthopedics department (60%), and 65% of elderly individuals who were hospitalized for falling were diagnosed with fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Another report from Japan declared that more than 40% of falls among the elderly caused fractures 23 . Our results revealed that most hospitalizations of elderly falling were treated by the orthopedics department (60%), and 65% of elderly individuals who were hospitalized for falling were diagnosed with fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, prevention of osteoporosis is a high-priority issue because osteoporotic fracture is one of the primary causes of elderly persons becoming bedridden ( 1 ). Measurement of bone mineral density (BMD) is the best tool available to assess osteoporotic fracture risk, since low BMD is an important risk factor for osteoporotic fracture ( 2 ).…”
mentioning
confidence: 99%
“…In Japanese women, hip fracture has been increasing every year and is affecting younger women. 18 Our results suggest that researchers should investigate methods of strengthening bone structures in the hip during TPTD treatment lasting more than 18 months. In previous reports, the efficacy of TPTD was indicated, particularly for increasing BMD.…”
Section: Discussionmentioning
confidence: 80%